1978
DOI: 10.1063/1.90441
|View full text |Cite
|
Sign up to set email alerts
|

Edge effect in high-resolution scanning Auger-electron microscopy

Abstract: Articles you may be interested inHigh-resolution transmission electron microscopy of as-deposited boron nitride on the edge of ultrathin Si flake An edge effect observed in high-resolution scanning Auger-electron microscopy is modeled by Monte Carlo methods based on the direct simulation of individual inelastic scattering processes. The Monte Carlo method permits the simulation of the spatial distribution of excited electrons generated by inelastic scattering. The results suggest that high-energy excited ("sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 2 publications
3
12
0
Order By: Relevance
“…The results from the simulations are in agreement with the earlier work (Shimizu et al 1978) that reported edge enhancements of Auger peak heights near the sharp edges of somewhat wider lines. Also, the new results reported here, using a narrower line, six differently aligned detectors, and a 100 nm beam, show that the least distortion of the true chemical profile is provided by those detectors with the smallest polar angles that are also aligned on the opposite side of the block from the electron source.…”
Section: Finite Length Sio 2 Block On Sisupporting
confidence: 93%
See 1 more Smart Citation
“…The results from the simulations are in agreement with the earlier work (Shimizu et al 1978) that reported edge enhancements of Auger peak heights near the sharp edges of somewhat wider lines. Also, the new results reported here, using a narrower line, six differently aligned detectors, and a 100 nm beam, show that the least distortion of the true chemical profile is provided by those detectors with the smallest polar angles that are also aligned on the opposite side of the block from the electron source.…”
Section: Finite Length Sio 2 Block On Sisupporting
confidence: 93%
“…When the 0.1 nm beam scans the end of the SiO 2 block, a considerable enhancement of the signal can be seen in Figure 7 (linescan C). This is related to the effect observed at normal incidence by Shimizu et al (1978) and El Gomati et al (1988). A step or even a small peak (Fig.…”
Section: Fig 4 (A)mentioning
confidence: 89%
“…However, the contrast for substrate Auger signals decreases consistently with increasing primary energy. This is due to the edge effect and backscattering effect that mentioned previously (El Gomati et al, 1988;Shimizu & Everhart, 1978;Tuppen & Davies, 1985). Both of these two effects can reduce the intensity difference of the Cu-Auger electrons when a primary beam scans over a particle.…”
Section: Resultsmentioning
confidence: 99%
“…While it has also been pointed out that (Ito et al, 1996) electrons with high energy will penetrate deep into the particle to reduce edge effect. The edge effect can dramatically degrade spatial resolution (El Gomati et al, 1988;Shimizu & Everhart, 1978;Tuppen & Davies, 1985) because AE from substrate can be detected even when the primary beam is impacted at the particle. At lower primary energies, it is more difficult for electrons to pass through the side surface of a particle and to hit the surrounding substrate surface for producing the edge effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation